Impact Of The Aris Module (Anxiety And Depression Reduction Through Islamic Spiritual Care) On Patients With Coronary Heart Disease - Wisuda, Aris Citra; Tukimin bin Sansuwito; Citra Suraya; Helsy Desvitasari (Citra Internasional Institute, 2024)
Background: Coronary heart disease (CHD) is a significant health issue that causes both physical and psychological distress, including heightened anxiety and depression. Islamic-based spiritual care practices may improve mental well-being in CHD patients. Objectives: This study aims to evaluate the effectiveness of the ARIS Module (Anxiety and Depression Reduction through Islamic Spiritual Care) in reducing anxiety and depression among CHD patients. Methods: Conducted from September to October 2024 at Siti Khadijah Islamic Hospital in Palembang, the study included 84 CHD patients, divided into an intervention group (42) and a control group (42), selected through purposive sampling. A pre- and post-intervention design was used to assess anxiety and depression levels before and after the ARIS Module, which incorporates Islamic spiritual practices such as guided prayer, reflection, and recitation. Results: The intervention group showed a statistically significant reduction in anxiety and depression levels. Patients also reported increased peace, spiritual connection, and emotional stability, enhancing their coping abilities and overall quality of life. Conclusions: The ARIS Module effectively reduced anxiety and depression in CHD patients, highlighting the value of integrating spiritual care into CHD treatment for mental and emotional health. Suggestions: It is recommended to incorporate programs like ARIS module into healthcare settings, with further research to explore its impact across diverse patient populations.